THE EFFECTIVENESS OF ISOMETRIC HANDGRIP AND WALKING EXERCISES ON BLOOD PRESSURE IN ELDERLY PATIENTS WITH HYPERTENSION - Rahmawati, Erni; Lily Herlinah; Nurhayati; Dhea Natashia; Syamsul Anwar (Universitas Kadiri, 2025)
Hypertension in the elderly is one of the global health challenges with a high prevalence. This study aims to evaluate the effectiveness of isometric handgrip exercise and walking exercise in reducing blood pressure in the elderly with hypertension. The research method used a quasi-experimental design with three intervention groups: (1) isometric handgrip exercise, (2) walking exercise, and (3) a combination of both. A total of 36 elderly were randomly selected and equally divided into the three groups. The intervention was conducted for eight weeks with analysis using Shapiro Wilk test, One Way Anova and Wilcoxon Test The results showed that the isometric handgrip and combination exercise groups had a significant decrease in systolic and diastolic blood pressure (p<0.05). Meanwhile, walking exercise also had a positive effect, although not significant in all weeks of evaluation. The combination of both interventions showed the most optimal results, especially at weeks 5 and 8. This study concludes that isometric handgrip exercise and its combination with walking exercise are effective for lowering blood pressure in elderly with hypertension. It is recommended that this intervention be applied as a non-pharmacological therapy in elderly health services, with assistance by health workers to improve compliance and effectiveness of the program.